2016
DOI: 10.1111/tpj.13163
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple lipid genes with modifications in expression and sequence associated with the evolution of hydroxy fatty acid accumulation in Physaria fendleri

Abstract: Two Brassicaceae species, Physaria fendleri and Camelina sativa, are genetically very closely related to each other and to Arabidopsis thaliana. Physaria fendleri seeds contain over 50% hydroxy fatty acids (HFAs), while Camelina sativa and Arabidopsis do not accumulate HFAs. To better understand how plants evolved new biochemical pathways with the capacity to accumulate high levels of unusual fatty acids, transcript expression and protein sequences of developing seeds of Physaria fendleri, wild-type Camelina s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 138 publications
10
53
0
Order By: Relevance
“…This mutant has higher levels of 18:1 substrate for the hydroxylation reaction because it fails to elongate 18-to 20-carbon FA, but the experiment created only a small increase in HFA, from 13% to 17% of the seed oil (Lu et al, 2006). Limited success of such efforts to increase both enzyme and substrate concentrations as well as RNA sequencing data (Horn et al, 2016) suggest that expression of the castor hydroxylase alone will not achieve levels of HFA accumulation sufficient for commercial development of crops.…”
mentioning
confidence: 99%
“…This mutant has higher levels of 18:1 substrate for the hydroxylation reaction because it fails to elongate 18-to 20-carbon FA, but the experiment created only a small increase in HFA, from 13% to 17% of the seed oil (Lu et al, 2006). Limited success of such efforts to increase both enzyme and substrate concentrations as well as RNA sequencing data (Horn et al, 2016) suggest that expression of the castor hydroxylase alone will not achieve levels of HFA accumulation sufficient for commercial development of crops.…”
mentioning
confidence: 99%
“…This indicate that there is an evolutionary advantage for the plant to contain the unusual fatty acid in the oil and that the magnitude of this advantage has increased simultaneously with the stepwise increase in the amount of this fatty acid that must have taken place throughout evolution. A recent analysis of genes expressed during seed development in Physaria fendleri that accumulates ~60% hydroxy fatty acids and a closely related Brassicaceae species, Camelina sativa , concluded that there are likely more than 20 genes within several lipid pathways that co‐evolved to facilitate high unusual fatty acid levels (Horn et al ., ). Vernolic acid, an epoxy fatty acid, is present in seed oils in plants from many orders.…”
Section: Resultsmentioning
confidence: 97%
“…The highest levels of hydroxy fatty acids in Arabidopsis and Camelina were reported at 29% and 21% of total fatty acid content, respectively (5,16). A comparison of global gene expression profiles from closely related Camelina to hydroxy fatty acid-accumulating developing seeds of Physaria fendleri suggested coevolution of many lipid biosynthetic genes and others associated with the production of hydroxy fatty acids (17). Furthermore, multiple differences in developmental timing of gene expression, substrate promiscuity by enzymes, allelic variation, ploidy, etc., likely contribute to differences in lipid composition among host systems.…”
Section: Plants As Chemical Feedstock Factoriesmentioning
confidence: 97%
“…Data points represent individual reports of GM crops or Arabidopsis accumulating hydroxy fatty acids. Data are adapted from table S1 of Horn et al(17).…”
mentioning
confidence: 99%